Vacancy spatial distribution causes different magnetism in graphene. Issue 6 (24th March 2012) - Antonov, Vladislav; Borisova, Dobrina; Proykova, Ana; Gidopoulos, Nikitas I.; Theophilou, Andreas K.
Abstract Recent reliable experiments have reported magnetism in defective graphene while the perfect one is nonmagnetic. In this work, we study the role of the vacancy concentration and spatial distribution on the orientation and magnitude of the magnetic moments induced by the defects with the help of the Quantum Espresso code, which is a plane‐wave implementation of the density functional theory. In the case of more than one vacancy per supercell, interaction between the total magnetic moments at each defective site occurs. The interaction is ferromagnetic for vacancies in the same sublattices and it is antiferromagnetic for the case of different sublattices. © 2012 Wiley Periodicals, Inc.